“No bastan muros de piedra para hacer una prisión” la vida cotidiana de los internos de la cárcel Villahermosa, Cali, Colombia (2014)
The current article, derived from a piece of research, describes the prison situation in Colombia, in the last few years, making emphasis on the particular overcrowding situation at “Villahermosa” Prison in the city of Cali, Colombia. Lastly, an analysis of the daily living conditions at that prison is made